VCP5-DCV : vmware certified professional-data center virtualization on vSphere 5.5 : study guide : exam VCP-550 - Atkinson, G. B. J. (Sybex Wiley, 2014)
Prepare yourself for VMware's challenging VMware Certified Professional-Data Center Virtualization exam, as well as the typical tasks and responsibilities you can expect as a VMware vSphere 5.5-certified professional. This comprehensive book guides you through all topics and objectives you'll need to know for the exam: prepares certification candidates for the VMware Certified Professional-Data Center Virtualization exam (VCP-DCV); covers all exam objectives; features real-world scenarios, hands-on exercises, and challenging review questions; explores key topics such as securing vCenter and ESXi, planning and configuring vSphere networking and storage, creating and deploying virtual machines and vApps, establishing services levels, and more. --